2000
DOI: 10.1590/s0100-879x2000000500006
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Fos protein immunoreactivity by spinal cord contusion

Abstract: The objective of the present study was to identify neurons in the central nervous system that respond to spinal contusion injury in the rat by monitoring the expression of the nuclear protein encoded by the c-fos gene, an activity-dependent gene, in spinal cord and brainstem regions. Rats were anesthetized with urethane and the injury was produced by dropping a 5-g weight from 20.0 cm onto the exposed dura at the T10-L1 vertebral level (contusion group). The spinal cord was exposed but not lesioned in anesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…IEGs have been used to monitor neuronal responds to peripheral nerve and spinal cord injury (Yakovlev and Faden 1994;Broude et al 1997;Ruggiero et al 1997;Del-Bel et al 2000). Fos and Jun have most often been used as histological markers for neuronal activation as they are induced by a wide range of mechanical stimuli, including spinal cord transection, sciatic nerve chronic constriction injury, sciatic nerve transection, sciatic nerve crush, and noxious mechanical stimulation (Chi et al 1993;Kajander et al 1996;DunnMeynell and Levin 1997;Ikeda and Nakagawa 1998;Hughes et al 1999).…”
Section: Easy and Reproducible Performance: Neuron Cell Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…IEGs have been used to monitor neuronal responds to peripheral nerve and spinal cord injury (Yakovlev and Faden 1994;Broude et al 1997;Ruggiero et al 1997;Del-Bel et al 2000). Fos and Jun have most often been used as histological markers for neuronal activation as they are induced by a wide range of mechanical stimuli, including spinal cord transection, sciatic nerve chronic constriction injury, sciatic nerve transection, sciatic nerve crush, and noxious mechanical stimulation (Chi et al 1993;Kajander et al 1996;DunnMeynell and Levin 1997;Ikeda and Nakagawa 1998;Hughes et al 1999).…”
Section: Easy and Reproducible Performance: Neuron Cell Bodiesmentioning
confidence: 99%
“…Research indicated that at 2.5 h post-transection, a large number of neurons containing c-Fos were observed in spinal transected animals but not in intact animals (Ruggiero et al 1997). For other types of mechanical injury to the spinal cord, such as contusion, the same time course of c-Fos expression was observed (Del-Bel et al 2000). The activation of c-Jun has been correlated with both the regeneration of nerve fibers and the mediation of neuronal death (Ham et al 1995;Hirata et al 1998).…”
Section: Easy and Reproducible Performance: Neuron Cell Bodiesmentioning
confidence: 99%
“…Animals were anesthetized by intraperitoneal injection of 250 mg/kg 2,2,2-tribromoethanol (Aldrich Chemical Company Inc., Milwaukee, WI, USA). After shaving the skin, animals were kept in a David Kopf stereotaxic apparatus and an incision was made in the skin and underlying muscles of the mid-thoracic region (14). Muscles were retracted and a mid-thoracic laminectomy was performed (vertebral segments T 10 -L 1 ).…”
Section: Surgical Preparationmentioning
confidence: 99%
“…The animals were placed on a hot-plate maintained at 52 ± 0.5ºC. The thermal nociceptive threshold was defined as the time required to elicit a hind paw lick or a jump (14). The cut-off time was 20 s.…”
Section: Behavioral Tests Of Functional Deficitsmentioning
confidence: 99%
See 1 more Smart Citation